2016
DOI: 10.1093/jme/tjw141
|View full text |Cite
|
Sign up to set email alerts
|

Aedes aegypti(Diptera: Culicidae) Longevity and Differential Emergence of Dengue Fever in Two Cities in Sonora, Mexico

Abstract: Dengue virus, primarily transmitted by the Aedes aegypti (L.) mosquito, has rapidly expanded in geographic extent over the past several decades. In some areas, however, dengue fever has not emerged despite established Ae. aegypti populations. The reasons for this are unclear and have sometimes been attributed to socio-economic differences. In 2013 we compared Ae. aegypti adult density and population age structure between two cities in Sonora, Mexico: Hermosillo, which has regular seasonal dengue virus transmis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 28 publications
0
23
0
1
Order By: Relevance
“…Adult Ae. aegypti populations in Hermosillo, have been shown to remain low until September/October, coinciding with peak transmission (Ernst et al, 2016).…”
Section: Dengue Epidemiology and Vector Ecologymentioning
confidence: 99%
“…Adult Ae. aegypti populations in Hermosillo, have been shown to remain low until September/October, coinciding with peak transmission (Ernst et al, 2016).…”
Section: Dengue Epidemiology and Vector Ecologymentioning
confidence: 99%
“…Eight studies modelled dengue transmission dynamics [184191]. Lee et al [192] constructed a predictive model that accurately foresaw 75% of dengue outbreaks in Colombia. Reiner et al [184] reported that social proximity drives fine-scale heterogeneity in dengue transmission rates based on data from Peru.…”
Section: Resultsmentioning
confidence: 99%
“…Hatching rate was found to be affected by population density and climate, and presence of vectors was associated with dengue incidence [209]. Ernst et al [192] found no correlation between Ae. aegypti density and human age structure between two cities with different dengue transmission dynamics.…”
Section: Resultsmentioning
confidence: 99%
“…barbirostris dengan perkiraan umur 9,82 hari dengan peluang hidup per hari sebesar 90%. Dari angka tersebut diketahui bahwa umur dari tiga jenis nyamuk tersebut relatif lebih lama dari masa inkubasi e k s t r i n s i k , s e h i n g g a p a r a s i t b i s a menyelesaikan siklus hidupnya di dalam tubuh nyamuk dan kemampuan bertelur yang 25 semakin banyak. Masa inkubasi ekstrinsik ilariasis B. malayi dari stadium L1 menjadi L3 26 adalah 6-6,5 hari, namun ketika jumlah larva ilarial terlalu banyak ditubuh nyamuk maka akan memakan waktu lebih lama (9-13 2 7 hari), sehingga berdasarkan data yang diperoleh untuk wilayah Kalimantan Tengah menunjukkan bahwa yang memenuhi syarat sebagai nyamuk potensial vektor ilariasis B. malayi di Kabupaten Kapuas adalah Ma.…”
Section: Analisa Dataunclassified